Substantial excretion of digoxin via the intestinal mucosa and prevention of long-term digoxin accumulation in the brain by the mdr 1a P-glycoprotein. - Mayer, U. (1996)
1. We have used mice with a disrupted mdr 1a P-glycoprotein gene (mdr 1a (-/-) mice) to study the role of P-glycoprotein in the pharmacokinetics of digoxin, a model P-glycoprotein substrate. 2. [3H]-digoxin at a dose of 0.2 mg kg-1 was administered as a single i.v. or oral bolus injection. We focussed on intestinal mucosa and brain endothelial cells, two major pharmacological barriers, as the mdr 1a P-glycoprotein is the only P-glycoprotein normally present in these tissues. 3. Predominant faecal excretion of [3H]-digoxin in wild-type mice shifted towards predominantly urinary excretion in mdr 1a (-/-) mice. 4. After interruption of the biliary excretion into the intestine, we found a substantial excretion of [3H]-digoxin via the gut mucosa in wild-type mice (16% of administered dose over 90 min). This was only 2% in mdr 1a (-/-) mice. Biliary excretion of [3H]-digoxin was not dramatically decreased (24% in wild-type mice versus 16% in mdr 1a (-/-) mice). 5. After a single bolus injection, brain levels of [3H]-digoxin in wild-type mice remained very low, whereas in mdr 1a (-/-) mice these levels continuously increased over a period of 3 days, resulting in a approximately 200 fold higher concentration than in wild-type mice. 6. These data demonstrate the in vivo contribution of intestinal P-glycoprotein to direct elimination of [3H]-digoxin from the systemic circulation and to the pattern of [3H]-digoxin disposition, and they underline the importance of P-glycoprotein for the blood-brain barrier.